KEMAMPUAN MENULIS ANAK YANG MEMILIKI GANGGUAN SPEKTRUM AUTISTIK - UTOYO, SETIYO (PPs UNJ, 2011)
The purpose of this case study is to try to obtain the data in describing the early writing skills through occupational therapy approaches in kindergarten children who have autistic spectrum disorders. The research was conducted at the Rainbow Kindergarten Special Needs Son Tangerang to the subject of autistic children aged 5-8 years who underwent occupational therapy. The method in this study using a case study with data collection through observation, documentation and writing skills beginning asessmenin children.Results showed that children with autistic spectrum disorders have a different beginning writing skills in accordance with the characteristics of each child both aspects of behavior, fine motor, attention and concentration as well as the level of language comprehension. Impact accompaniment of the results showed that an increase in learning, especially in the beginning after the childs writing skills through occupational therapy.Keywords: writing skills, autistic spectrum, occupational therapyÂ